Influencing Factors and Effects of Treatment on Quality of Life in Patients With Gastric Cancer—A Systematic Review - Rupp, Sophia Kristina; Stengel, Andreas (Frontiers in Psychiatry, 2021)
Background: Gastric cancer (GC) is one of the leading causes of death worldwide. It is associated with several disease-related impairments contributing to the psycho-social burden of those patients, such as deterioration of well-being and overall quality of life (QOL). The aim of this study is to present the wide range of factors potentially impacting patients’ overall well-being and possible preventive interventions. Methods: This systematic review was conducted in October 2020 with a search in the PubMed, MedLine, PsycInfo and Google Scholar databases. We used the keywords “gastric cancer”, “gastric neoplasm” and each of them combined with “quality of life”, “depression” and “anxiety” to identify all relevant articles reporting about potential impact factors influencing the overall well-being of patients suffering from gastric cancer. Results: Finally, 125,490 articles were found, of which 125,431 were excluded in several steps of screening. Inclusion criteria were studies carried out on human ≥ 18 years of age, studies in English or German language, clinical trials, registry-based studies, cohort studies, population-based studies and certain titles and abstracts. After screening for eligibility 35 potential factors influencing overall well- being in patients with GC were identified and classified into 9 important categories: genetic condition, treatment method, blood markers, nutritional status, daily living, state of health, mental state, supportive care, and alternative treatment. Conclusion: Since various factors are involved in the development of patients’ overall well-being, timely treatment of psycho-social impairments by physicians and psychologists is of enormous importance. Preventing psycho-social burden by improving patients’ QOL should be of high importance in the treatment regimen of patients with GC.